Dr. Margaret McKinnon - Dong, Audrey; Grignano, Veronica (The Meducator, 2024)
I’m the Homewood Chair of Mental Health & Trauma and a Professor and the Associate Chair of Research in the Department of Psychiatry and Behavioral Neurosciences at McMaster. I’m also a licensed clinical neuropsychologist. My interest in trauma and mental health research stands both from longstanding academic work and my own personal experience. Over 20 years ago, I was onboard an aircraft that ran out of fuel midway over the Atlantic and we were prepared for the ditching of the aircraft. Fortunately, we made it to a military airstrip where we made a rough landing. The back of the plane was on fire and we evacuated. I developed post-traumatic stress disorder (PTSD) following that incident. This shifted my area of interest from working in aging and dementia to mental health and wellbeing. I’m really grateful for the treatment that I received but also the opportunity to give back. It’s really important to challenge the stigma around mental health.